Absence from Work of the Self-Employed: A Comparison with Paid Employees - Lechmann, Daniel; Schnabel, Claus (Kyklos, 2014)

Are the self-employed really jacks-of-all-trades? Testing the assumptions and implications of Lazear’s theory of entrepreneurship with German data - Lechmann, Daniel; Schnabel, Claus (Small Business Economics, 2014)

Can working conditions explain the return-to-entrepreneurship puzzle? - Lechmann, Daniel (Journal for labour market research, 2015)

Coming to work while sick: An economic theory of presenteeism with an application to German data - Hirsch, Boris; Lechmann, Daniel; Schnabel, Claus (Oxford Economic Papers, 2017)
Presenteeism, i.e. attending work while sick, is widespread and associated with significant costs. Still, economic analyses of this phenomenon are rare. In a theoretical model, we show that presenteeism arises due to differences between workers in (health-related) disutility from workplace attendance. As these differences are unobservable by employers, they set wages that incentivise sick workers to attend work. Using a large representative German data set, we test several hypotheses derived from our model. In line with our predictions, we find that bad health status and stressful working conditions are positively related to presenteeism. Better dismissal protection, captured by higher tenure, is associated with slightly fewer presenteeism days, whereas the role of productivity and skills is inconclusiv
Keywords: presenteeism; absenteeism; sick leave; Germany

Die geschlechtsspezifische Verdienstlücke in selbstständiger Erwerbstätigkeit - Lechmann, Daniel (Die Vielfalt der Selbständigkeit. Sozialwissenschaftliche Beiträge zu einer Erwerbsform im Wandel, 2014)

The dynamics of solo self-employment: Persistence and transition to employership - Lechmann, Daniel; Wunder, Christoph (Labour Economics, 2017)

Why is there a gender earnings gap in self-employment? A decomposition analysis with German data - Lechmann, Daniel; Schnabel, Claus (IZA Journal of European Labor Studies, 2012)
Using a large data set for Germany, we show that both the raw and the unexplained gender earnings gap are higher in self-employment than in paid employment. Applying an Oaxaca-Blinder decomposition, about one quarter to one third of the difference in monthly self-employment earnings can be traced back to women working fewer hours than men whereas there are no robust segregation effects. Working time flexibility and career aspirations do not seem to contribute much to the gender earnings gap, whereas family background plays a certain role as it affects the earnings of self-employed men and women quite differentl
WiSo-Import:2015-03-26:4085
Keywords: Earnings differential; Gender pay gap; Germany; Self-employment